Output-unemployment asymmetry in Okun coefficients for OECD countries - Boďa, Martin; Povazanova, Mariana (Elsevier Science BV, 2021)
Different asymmetries in Okun's law for 21 OECD countries over the period 1989-2019 are studied in the paper. To this end, an extended Okun equation accommodating possibly differentiated responsiveness to output and unemployment fluctuations is formulated applicable not only at the level of a whole economy, but also separately to gender-specific parts of the labor market in a system framework. For most of the countries, Okun's law asserts itself with a greater magnitude in years when output recedes than in those when it grows. In nearly all the countries, Okun's law is found stronger with decreases in unemployment and weaker or offset with rising unemployment. Finally, in the majority of the countries, male unemployment is more sensitive to output fluctuations than female unemployment, or there is no significant difference whatsoever. (c) 2020 Economic Society of Australia, Queensland. Published by Elsevier B.V. All rights reserved.
Asymetrie mezi výstupem a nezaměstnaností v Okunových koeficientech pro země OECD
Keywords: Okun's law; difference version; asymmetry; output-unemployment regimes; Okunův zákon; diferenční verze; asymetrie; režimy výstupu a nezaměstnanosti